Pengaruh senam aerobik low impact terhadap peningkatan kualitas hidup perempuan menopause - Nurlina Ina; Ova Emilia; Herlin Fitriani Kurniawati (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2017)
Abstract: Various efforts can be made to overcome the symptomsand complaints that occur in menopausal women, one of themwith aerobic low impact exercise. The aim of research to determinethe effect of aerobiclow impact exercise to improvement the qualityof life of menopausal women. This type of research quasyexperiment with non-equivalent pretest and posttest control groupdesign. The sampling technique used purposive sampling methodwith a sample size of 56 respondents. The analysis used is theindependent t test and paired sample t test with significance levelof 95%. The results of research shows that there is an increasedquality of life scores menopausal women who do aerobic low impactexercise than those who do not do aerobic low impact exercise,with p value 0.05.